Constructing complex Cognitive Discourse Functions in higher education: An exploratory study of exam answers in Spanish- and English-medium instruction settings. (November 2017) - Breeze, Ruth; Dafouz, Emma
Abstract: The present paper applies the recently developed construct of the Cognitive Discourse Function (CDF) in the context of student writing at tertiary level, using it to explore differences in exam performance between high and low-level answers, and between L1 (Spanish) and L2 (English) classrooms. We analyse the exam answers from two Business Administration cohorts (n = 30) at a large Spanish university who had taken the same content course with the same teacher in one of the two languages. Results suggest that the high-level exams, whether in Spanish (L1) or in English (EMI), succeeded in providing explicit responses to the combination of DESCRIBE-CLASSIFY and DESCRIBE-EXPLAIN CDFs requested in the exam questions. In contrast, the low-level exams usually failed to make meaningful and overt connections between the CDFs activated and their linguistic realisations, irrespective of the language used. These findings suggest that while academic literacy may be less developed in students' L2, it should be systematically addressed in both learning contexts. In our conclusions, we evaluate how the CDF construct sheds light on language demands in specific content areas, we argue for its utility in EMI settings, and we make some concrete pedagogical recommendations to scaffold student writing and increase content specialists' language awareness.